Molecular cloning and expression analysis of CDK genes during selective and wild populations of juvenile Meretrix meretrix. (9th August 2022) - Wu, Yangping; Chen, Suhua; Chen, Aihua; Li, Qiujie; Zhang, Yu; Cao, Yi; Zhang, Zhidong; Tian, Zhen
Abstract: The saltwater hard clam Meretrix meretrix is an important commercially bivalve in China. Therefore, identification of key genes involved in growth regulation are the primary prerequisites for further development of phenotype‐selective breeding of the clams and understanding molecular mechanisms of growth regulation. In the present study, we cloned the full‐length cDNA sequences of the growth‐related genes cyclin‐dependent kinase 1 and 7 in M. meretrix ( MmCDK1 and MmCDK7 ) and then investigated their gene expression characteristics and associations with growth traits. The full‐length cDNA of MmCDK1 was 1623 base pairs (bp), with a 900 bp open reading frame (ORF) encoding 299 amino acids. The full‐length MmCDK7 cDNA was 1296 bp, with a 1017 bp ORF encoding 338 amino acids. In adult clams, expression levels of MmCDK1 and MmCDK7 were significantly higher in the gonad than other tissues ( p  < 0.05). In the eight developmental stages of M. meretrix, MmCDK1 and MmCDK7 had the highest expression levels in the multicellular stage, followed by oosperm, blastula stage and gastrulae stage. The BLAST searches showed that MmCDK1 has high similarity to the cyclin‐dependent kinases from Crassostrea gigas (89.26%), and the protein structure of MmCDK7 was similar to the Mizuhopecten yessoensis (75.00%). In addition, the growth trait (shell length) of clams was tested in different cultivation conditions. A 2 × 2 layout was designed including four treatment groups were abbreviated as LH FH (high light and high food), LH FL (high light and low food), LL FH (low light and high food) and LL FL (low light and low food). The shell length of the selective and wild clams in the LH FH group was higher than those in other groups on the 75th day. Moreover, the shell length and MmCDK7 expression levels of the selective clams was higher in the LH FH, LL FH and LH FL groups than the wild clams on the 75th day, significantly ( p  < 0.05). However, the shell length and relative expression levels of MmCDK7 were no significant differences between the selective clams and the wild clams in the LL FL group ( p  > 0.05). MmCDK1 expression levels of the selective clams were higher than the wild clams in four treatment groups on the 75th day, significantly ( p  < 0.05). Further analysis showed that there was a significant linear correlation between shell length and relative expression levels of MmCDKs genes ( MmCDK1 and MmCDK7 ). These results suggest that MmCDK1 and MmCDK7 are key growth‐related genes, and they may have potential value in selective breeding to improve growth performance of M. meretrix .